Regulatory microRNAs and vascular cognitive impairment and dementia - Zhang, Jing (CNS Neurosci Ther, 2020)
Vascular cognitive impairment and dementia (VCID) is defined as a progressive dementia disease related to cerebrovascular injury and often occurs in aged populations. Despite decades of research, effective treatment for VCID is still absent. The pathological processes of VCID are mediated by the molecular mechanisms that are partly modulated at the post‐transcriptional level. As small endogenous non‐coding RNAs, microRNAs (miRs) can regulate target gene expression through post‐transcriptional gene silencing. miRs have been reported to play an important role in the pathology of VCID and have recently been suggested as potential novel pharmacological targets for the development of new diagnosis and treatment strategies in VCID. In this review, we summarize the current understanding of VCID, the possible role of miRs in the regulation of VCID and attempt to envision future therapeutic strategies. Since manipulation of miR levels by either pharmacological or genetic approaches has shown therapeutic effects in experimental VCID models, we also emphasize the potential therapeutic value of miRs in clinical settings.